Role of Vaitarana Basti in the Management of Amavata w.s.r. to Rheumatoid Arthritis – A Case Study - Kaushik, Jyoti; Kumar, Ajay; Yadav, Pratima (International Research Journal of Ayurveda & Yoga, 2021)
Musculoskeletal problems are a rapidly increasing issue for adult population. It not only affects the human’s body movement but also quality of lifetime of a well-being. Aamvata is disease of Ama and vata where vitiation of vata with accumulation of Ama is main pathogenesis. In modern science Aamvata is much similar to Rheumatoid Arthritis due to similarity of some signs and symptoms. Ayurveda is taken into account because the science which not only cure the disease but also stop the reoccurrence of disease. Ayurveda has become the most effective measure for treatment of Amavata as the other system don’t have any complete cure for this disease. In the present study a 17-year-old boy having complaint of bilateral Knee Joint pain, bilateral fingers joint pain, left elbow pain, left shoulder pain, anorexia, malaise, morning stiffness and difficulty in walking for 6 months. Patient having RA factor positive. Vaitarana basti with nearly vata shamana aushadhi is given to patients. He got relief in pain and stiffness within 5 days of basti and within 16 days he got marked improvement in symptoms. As earlier said Amavata is because of accumulation of Ama and vitiation of vata in our body and also said by Acharya Charak, basti is best treatment for vata dosha. So, here basti is suggested to patient.